Peningkatan Kemampuan Sains Anak Melalui Metode Eksperimen Balon Ilmiah Pada Anak Di Taman Kanak-kanak Islam Bunayya - Arbayah; Rosevina Saleh, Quinta; Sjamsir, Hasbi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2022)
The background of research at Bunayya Islamic Kindergarten is that there are still many children in the B1 group whose science skills are still lacking. Children are less motivated to discover new facts, explore and tackle discovered problems. Therefore, through experimental methods, scientific balloons can improve children's science skills in cognitive development. The formulation of the problem in this study is "Whether through the experimental method scientific balloons can improve science skills in group B1 children of Bunayya Islamic Kindergarten " Research at Bunayya Islamic Kindergarten includes a type of classroom action research using qualitative descriptive analysis techniques by summing, looking for the average value, midpoint and percentage so that the flow of thinking has been read through a table that describes the results of the assessment achieved by children. The object of research was 17 children in group B1 of Bunayya Islamic Kindergarten. Based on the results of research in the first cycle, the average number of grade grades of 838 and 49 was categorized as Starting to Develop with the percentage of children who obtained Developing as Expected scores of around 47% and Starting to Develop scores of around 53%. In cycle II, the average number of grade grades of 1053 and 62 was categorized as Developing as Expected with the percentage of children who obtained Very Good Development scores of around 12% and Developing as Expected scores of around 88%. From these results, it can be concluded that the scientific balloon experimental method improves science skills in group B1 children of Bunayya Samarinda Islamic Kindergarten.